Physical and chemical modification of lignocellulosic waste biomass-tool for improving sorption capacity - Zorica Lopičić; Tatjana Šoštarić; Jelena Milojković; Marija Mihajlović; Jelena Petrović; Ivan Antanasković; Mirjana Stojanović (Journal of Engineering & Processing Management, 2018)
The main constituents of ligno-cellulosic (LC) biomass are lignin, celluloses and hemicelluloses, complex polymers with many functional groups, which can be modified with the purpose to improve the sorption properties of the starting material. This paper presents several physical and chemical modifications applied to LC biomass of peach stones (Prunus persica L.), abundant waste from food industry. These stones were firstly mechanically activated in two mill types, and then by different chemicals. Sorption experiments were performed in batch reaction system with stirring. Cu(II) sorption kinetic was tested through three reaction kinetic models: pseudo-first order, pseudo-second order and Elovich equation. FT-IR analyses of chemically modified samples is alsopresented and discussed.
Keywords: peach stones; modification; sorption; kinetics; FT-IR